Anatomy of the Naga City Landslide and Comparison With Historical Debris Avalanches and Analog Models - Lagmay, Alfredo Mahar Francisco; Escape, Carmille Marie; Ybañez, Audrei Anne; Suarez, John Kenneth; Cuaresma, Genaro (Frontiers in Earth Science, 2020)
4 Debris avalanches pose some of the most destructive geologic hazards that threaten both 5 urban and rural populations around the world. On 20 September 2018, villages in Naga City, 6 Cebu, Philippines, were devastated by a landslide that claimed 78 lives with 6 missing, joining 7 other catastrophic landslides in the country like the 1628 Iriga and the 2006 Guinsaugon debris 8 avalanches. Understanding the mechanism of these gargantuan landslides and their correct 9 nomenclature are useful for hazard prevention and mitigation. In this study, we compare the 10 deposit characteristics of the Naga City landslide with analog models and well-known historical 11 debris avalanche events/deposits in the Philippines to understand factors that led to the landslide 12 disaster in Naga City. Physical characteristics obtained from aerial and satellite imagery, ground 13 surveys, recorded footage, borehole data, and lithologic maps provided a detailed dataset for 14 analyzing the conditions that led to the mass movement and the observed characteristics of 15 the Naga landslide deposits. Comparison with analog models of hummock formation and the 16 description of historical debris avalanche deposits show striking similarities, which were used 17 to demonstrate that the Naga landslide was a Rockslide-Debris Avalanche. The equations of 18 Corominas (1996) and Dade and Huppert (1998) for long-runout rockfalls support this analysis. 19 The Naga landslide event is an example of a well-documented debris avalanche, complete with 20 all the characteristics of this type of rapid mass movement. It is consistent with the descriptions 21 found in the literature with respect to its deposit features and mechanical behavior as de.ned by 22 laboratory models and empirically-derived equations. This study helps us understand historical 23 and future long-runout debris avalanches in order for scientists and authorities to .nd ways to 24 save lives. Unfortunately, there was lack of appropriate hazards assessment on the site, which 25 had warnings in the form of the development of fractures at the headscarp of the landslide, a 26 month prior to the disaster.